2018
DOI: 10.1021/acs.jpclett.8b02327
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Thermally Activated Delayed Fluorescence Materials: The Challenges Ahead

Abstract: Thermally activated delayed fluorescence (TADF) offers the premise for all-organic light emitting diodes with quantum efficiencies competing those of transition metal-based phosphorescent devices. While computational efforts have so far largely focused on gas-phase calculations of singlet and triplet excitation energies, the design of TADF materials requires multiple methodological developments targeting among others a quantitative description of electronic excitation energetics, fully accounting for environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
188
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(222 citation statements)
references
References 108 publications
1
188
0
5
Order By: Relevance
“…V SOC is calculated to have a mean absolute value of ≈0.01 meV (i.e., ≈0.1 cm −1 ), which is on the lower end of the values reported for typical TADF molecules (0.02-0.10 meV). [61] In line with the results for other TADF molecules, [53] the V SOC values correlate approximately linearly with the ΔE ST values (V SOC ∝ ΔE ST , Figure 7a). This underlines that an increase in V SOC value comes at the expense of an increase in the barrier for the RISC transition.…”
Section: Intersystem Crossing Transitionssupporting
confidence: 85%
See 2 more Smart Citations
“…V SOC is calculated to have a mean absolute value of ≈0.01 meV (i.e., ≈0.1 cm −1 ), which is on the lower end of the values reported for typical TADF molecules (0.02-0.10 meV). [61] In line with the results for other TADF molecules, [53] the V SOC values correlate approximately linearly with the ΔE ST values (V SOC ∝ ΔE ST , Figure 7a). This underlines that an increase in V SOC value comes at the expense of an increase in the barrier for the RISC transition.…”
Section: Intersystem Crossing Transitionssupporting
confidence: 85%
“…As shown in Figure 4b, over 52% of the molecules possess a Δ E ST less than 0.05 eV, ensuring that a considerable ratio of oBFCzTrz monomers can potentially exhibit significant reverse intersystem crossing rates at room temperature. It is worth mentioning that the Δ E ST values are found to be positive for all the structures considered here; previous studies on TADF emitters have indicated that intermolecular interactions can sometimes alter the relative positions of the S 1 to T 1 states, leading to negative Δ E ST values in the case of a few of the emitters …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…We are also aware of other technical requirements, such as: short excited-state lifetime to avoid non-radiative decay and thus maximize the photoluminescence quantum yields (PLQYs), appropriate color CIE coordinates and color purity, etc. However, in the following sections we focus on the basic aspects for the molecular modelling, at the molecular scale, related to energy conversion [10]. Molecules 2020, 25, x 3 of 11 Figure 2.…”
mentioning
confidence: 99%
“…[114,115] For an in-depth discussion about the range of validity and the challenges of quantum chemical calculations in OLEDs, e. g., vertical transition energies and DE ST in TADF compounds, we invite interested readers to see another recent review. [116] In the aspect of modeling molecular orientation, we would like to point out that careful force-field parametrization is of particular importance, especially for nonbonded interactions.…”
Section: Part 3: Computer Simulationsmentioning
confidence: 99%